2014
DOI: 10.1177/0363546514560880
|View full text |Cite
|
Sign up to set email alerts
|

Multirater Agreement of the Causes of Anterior Cruciate Ligament Reconstruction Failure

Abstract: Background ACL reconstruction failure occurs in up to 10% of cases. Technical errors are considered the most common cause of graft failure despite the absence of validated studies. There is limited data regarding the agreement among orthopedic surgeons in terms of the etiology of primary ACL reconstruction failure and accuracy of graft tunnel placement. Purpose The purpose of this study is to test the hypothesis that experienced knee surgeons have a high level of inter-observer reliability in the agreement o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
22
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 41 publications
1
22
0
1
Order By: Relevance
“…Unfortunately, neither bone tunnel position data nor knee laxity data after surgery were available to us for this study. However, work by Matava et al 30 demonstrated that 10 orthopaedic surgeons reviewing 20 cases of revision ACLR were unable to agree whether the cause of graft failure was due to malpositioning of the graft or by other mechanisms. Therefore, even if we had intraoperative and/or radiographic data on bone tunnel location, it is unclear if we would have the ability to establish the cause of graft failure.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, neither bone tunnel position data nor knee laxity data after surgery were available to us for this study. However, work by Matava et al 30 demonstrated that 10 orthopaedic surgeons reviewing 20 cases of revision ACLR were unable to agree whether the cause of graft failure was due to malpositioning of the graft or by other mechanisms. Therefore, even if we had intraoperative and/or radiographic data on bone tunnel location, it is unclear if we would have the ability to establish the cause of graft failure.…”
Section: Discussionmentioning
confidence: 99%
“…Improper surgical technique remains one of the most common sources of failure of primary ACL reconstructions. 1 , 10 , 28 , 30 , 38 , 42 Although careful surgical planning and knowledge of pertinent anatomical landmarks are key to prevent unexpected intraoperative complications, breach of the posterior or lateral cortex during reaming of the femoral tunnel remains one of the most challenging situations to properly address. Without thorough evaluation of the integrity of the femoral tunnel and posterior wall of the lateral femoral condyle, this complication can remain unrecognized and therefore place the graft at greater risk of failure due to loss of fixation or altered biomechanics.…”
Section: Causes Of Femoral Cortical Violation and Techniques For Avoimentioning
confidence: 99%
“…Recent literature has demonstrated that tunnel malposition is a common cause of both intraoperative complications and graft failure after ACLR. 1 , 4 , 7 , 10 , 30 , 42 …”
mentioning
confidence: 99%
“…3 However, despite the numerous surgical techniques described, ACLR improves the patient's activity level and reduces, but does not eliminate, the risk of joint degeneration and the necessity for further surgery. 2,3 Restoration of normal ACL anatomy requires anatomic remodeling, fiber maturation, and ligamentization of the applied graft. Early ACL remnantesparing techniques support the theory of preserving the proprioceptive receptors, enhancing the revascularization process, and finally, achieving "cellular ligamentization."…”
mentioning
confidence: 99%
“…1,2 In an effort to decelerate this degenerative process, arthroscopic anterior cruciate ligament reconstruction (ACLR) using tendon autografts has been one of the most popular surgical interventions worldwide. 3 However, despite the numerous surgical techniques described, ACLR improves the patient's activity level and reduces, but does not eliminate, the risk of joint degeneration and the necessity for further surgery. 2,3 Restoration of normal ACL anatomy requires anatomic remodeling, fiber maturation, and ligamentization of the applied graft.…”
mentioning
confidence: 99%